Tax Law in Slovakia under the Influence of Pandemic, Digital Transformation and Inflation - Štrkolec, Miroslav (Public Governance, Administration and Finances Law Review, 2023)
Tax law, as a branch of law belonging to the hard core of public law, is one of its branches that are characterised by instability rather than the stability of its rules. The reasons for the frequent changes in tax law can be found not only in political agendas and the economic view of taxes, but equally in external impacts, to which the legislature tries to respond promptly. The paper aims at clarifying the competing views on the position of tax law in the legal system and defining its functions, as they have been interpreted differently in different periods of social development. The paper then examines the significant changes in tax law in recent years, triggered by the Covid-19 pandemic, digital transformation and inflation, and assesses the extent to which these changes contribute to the fulfilment of the core, the fiscal function of taxes.